The predictive roles of boredom, depression, loneliness and self-esteem on phubbing behaviour among undergraduates in Malaysia - Letchumyesswary, Gunashekaran; Nivashini, Ragu (2022)
The developments in computer and Internet technology have led to increased communication and faster access to information. These advancements have increased reliance on smartphones which resulted in phubbing behaviour and this consequently will damage interpersonal relationships. However, research on the predictive roles of (a) boredom; (b) depression; (c) loneliness; (d) self-esteem on phubbing behaviour appear less. Therefore, the current research attempted to study the predictive roles of boredom, depression, loneliness, and self-esteem on phubbing behaviour among Undergraduates in Malaysia. The current research utilized Cognitive Behavioural Theory as its theoretical framework. The current cross-sectional study's purpose was to examine the predictive roles of boredom, depression, loneliness, and self-esteem on phubbing behaviour among Malaysian undergraduates. The cross-sectional study included 170 target individuals who were recruited via an online survey using the purposive sample method. However, for data analyses, only 161 responses were selected. The participants that were chosen met the requirements which were (i) Aged 18-30 years old (ii) Malaysian Undergraduate students (iii) smartphone users. The result of the present study showed that boredom, depression, and loneliness positively predict phubbing behaviour while self-esteem negatively predicts phubbing behaviour. Thus, the hypotheses of the current study were supported. In conclusion, this study has filled in the knowledge gap and provided information for future studies related to the predictive factor of phubbing behaviour. Parties’ concerned may also use the offered knowledge and information to develop and conduct effective intervention programs to reduce phubbing behaviour.